PERAN KEMAMPUAN KERJA DALAM MEMEDIASI PENGARUH ANTARA GAYA KEPEMIMPINAN, DUKUNGAN ORGANISASI, DAN KINERJA PEGAWAI BAPPEDA SIMEULEU - Herizal; Hasyim; Fatimah, Fatia (Universitas Bina Taruna Gorontalo, 2025)
This research aims to analyze the role of workability in mediating the influence between leadership style, organizational support, and employee performance at the Regional Planning and Development Agency (Bappeda) of Simeulue Regency. Quality human resources (HR) are the main factor in determining organizational effectiveness and efficiency. Therefore, this research examines how leadership style and organizational support can improve employee performance by increasing workability. The research method used is quantitative, using survey techniques via questionnaires given to Simeulue Regency Bappeda employees. Data were analyzed using descriptive statistical techniques and path analysis to test the relationship between variables. The research results show that leadership style and organizational support positively affect workability, which in turn improves employee performance. Employability proved to be a significant mediator in this relationship. These findings provide implications for organizational management in designing strategies to improve employee performance through effective leadership policies and optimal organizational support.